Why are fertilizer prices in Malawi high? And what can be done? - Duchoslav, Jan; Rusike, Joseph (International Food Policy Research Institute, 2021)
Malawi has a long history of public intervention programs in the fertilizer market, going back to 1992. The latest iteration, the Affordable Inputs Program (AIP), was launched in 2020 and is now under considerable strain because of rapidly escalating fertilizer prices. Under the AIP, the Govern-ment of Malawi intends to supply around 428,000 tons of fertilizer (half of it NPK, half urea) to small-holder farmers at a subsidized price of MWK 4,995 per 50 kg bag. It was envisaged that the fertilizer would be imported and distributed by private suppliers and two parastatals, the Smallholder Farm-ers Fertilizer Revolving Fund of Malawi (SFFRFM) and the Agricultural Development and Marketing Corporation (ADMARC). However, the Government found the cost proposed by the private sector through the Fertilizer Association of Malawi (MWK 35,000 per bag) excessive, and is considering sourcing all AIP fertilizer exclusively through SFFRFM and ADMARC. The purpose of this is to assess the situation and outline the best options available to the Government to ensure ade-quate fertilizer supply in the short time remaining before the onset of the agricultural season in Ma-lawi.